Rail Project's Needed Project Management Approaches, Strategies, Methodologies, and Processes - Steffi. R; R. Regin; S. Suman Rajest; Shynu T; Jerusha Angelene Christabel G (International Journal on Economics, Finance and Sustainable Development, 2022)
In order to successfully deliver Rail project business outcomes, this paper explores the necessary project management approaches, strategies, methodologies, and processes. As well as transitional resources and templates to adopt and improve change management throughout the project. The paper begins by discussing Rail's business environment using the rational structure methodology. And we observe several methods for mitigating danger. In addition, the study suggests the working framework as an approach for project management, planning, and preparation. The research into the Rail Project incorporates findings from all of these approaches. Methods for effective Plan administration and control are first discussed. Meetings and presentations are discussed, along with how crucial they are for understanding the current state of a project and making sound decisions moving forward. It details the methodology employed in arriving at a value judgement. This means it is the superior measuring stick for success and control.